Pengalaman Pembelajaran Transformatif Perempuan Dewasa Madya dalam Pencarian Makna Hidup Melalui Aktivitas Menulis - Safitri, Febriyanti Dwi; Hafina Adiwinata, Anne; Yulindrasari, Hani (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to explore transformative learning experiences of middle-aged women through writing activities in an Indonesian women's writing. Transformative learning among middle-aged women is crucial to investigate as this phase involves complex identity transitions, yet limited research explores the role of reflective writing in personal transformation processes within Indonesian contexts. This qualitative research employed Interpretative Phenomenological Analysis (IPA) involving two participants aged 41-64 years from the Padma Women Writers Community through in-depth interviews. Data analysis followed Mezirow's transformative learning framework to map participants' experiences. Findings reveal transformative learning processes beginning with disorienting dilemmas triggered by life transitions, followed by critical self-examination through reflective writing, exploration of new roles, and perspective transformation regarding empowerment and autonomy. Writing functions as a catalyst for transformation through three mechanisms: structured examination of experiences, narrative construction for meaning-making, and community sharing for validation. This research contributes to extending Mezirow's theory application in creative expression contexts and provides insights for developing reflective writing-based learning programs for middle-aged women.